Socio-Economic Status of Scheduled Tribes in Sonbhadra District, Uttar Pradesh - Gupta, Pratima; Bilas, Ram (National Geographical Journal of India, 2022)
This paper aim to investigate the socio-economic status of scheduled tribes dwelling in Sonbhadra district of Uttar Pradesh. Primary data is collected [stratified random sampling method] from 70 respondents of the tribal community of the district. They have their own distinctive cultural and social aspect but they are very backward in the view of socio-economic condition for centuries. They share 20.67 percent of the total population of the district yet they have remained outside the realm of the general development process due to their habitation in forests and hilly tracts. They are living very low paid life in spite of dwelling in the energy capital of India. Mostly respondents are uneducated with the literacy rate of 44.2 percent of the district. They are leading a miserable life of unskilled laborers. The survey reveals that the tribes of the study area have not got the full benefits of the development processes undertaken by the governments over more than past six decades. Mostly respondent are living under the heavy burden of private and government loans. There should be made more and more effective attempts to develop the social, economical and educational status of the tribal people living in Sonbhadra district so that they might be connected to the main stream of modern technical development process